2023
DOI: 10.1371/journal.ppat.1011160
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally active nasopharyngeal commensals and opportunistic microbial dynamics define mild symptoms in the COVID 19 vaccination breakthroughs

Abstract: The development of COVID 19 vaccines as an effort to mitigate the outbreak, has saved millions of lives globally. However, vaccination breakthroughs have continuously challenged the vaccines’ effectiveness and provided incentives to explore facets holding potential to alter vaccination-induced immunity and protection from subsequent infection, especially VOCs (Variants Of Concern). We explored the functional dynamics of nasopharyngeal transcriptionally active microbes (TAMs) between vaccination breakthroughs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Class Gammaproteobacteria belongs to phylum proteobacteria, the abundance and functional characterization of which have been mixed across studies. Devi et al identified significant difference at the class level of the phylum Proteobacteria in the COVID 19 vaccination breakthroughs, where Alphaproteobacteria and Betaproteobacteria were found transcendent in the unvaccinated patients while Gammaproteobacteria was found enriched in the vaccinated patients 40 . Evidence exists to support this finding which suggests that an increase of Gammaproteobacteria produces beneficial effects for favorable immune responses post vaccination 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Class Gammaproteobacteria belongs to phylum proteobacteria, the abundance and functional characterization of which have been mixed across studies. Devi et al identified significant difference at the class level of the phylum Proteobacteria in the COVID 19 vaccination breakthroughs, where Alphaproteobacteria and Betaproteobacteria were found transcendent in the unvaccinated patients while Gammaproteobacteria was found enriched in the vaccinated patients 40 . Evidence exists to support this finding which suggests that an increase of Gammaproteobacteria produces beneficial effects for favorable immune responses post vaccination 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas and Salmonella (also a member of the class Gammaproteobacteria ) were overrepresented in the COVID‐19 vaccination breakthrough. Gammaproteobacteria have been reported to be beneficial for a favorable immune response postvaccination 39 . The order Selenomonadales belongs to the class Negativicutes .…”
Section: Discussionmentioning
confidence: 99%
“…Gammaproteobacteria have been reported to be beneficial for a favorable immune response postvaccination. 39 The order Selenomonadales belongs to the class Negativicutes. Patients with human immunodeficiency virus (HIV) had a higher abundance of Negativicutes.…”
Section: Covid-19 Severitymentioning
confidence: 99%
“…Our prior studies have lit up the dynamics of commensal and opportunistic TAMs at various phases of disease severity and the quicker turnaround rate of patients who had received vaccinations. 13 , 17 To the best of our knowledge, this is the first study to characterize the TAMs composition and host-microbe dynamics across different variants of SARS-CoV-2, namely Pre-VOC, Delta, and Omicron, as well as the clinical outcomes of each group, recovery, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In yet another study by our group, the importance of commensal species including Streptococcus salivarius , Streptococcus dysgalactiae , and Pseudomonas alcaliphila were found in the milder presentation of the SARS-CoV-2 infected patients who received two doses of COVID-19 vaccine compared to unvaccinated & infected patients. 13 Many studies have demonstrated the superiority of commensal microbial composition over opportunistic pathogens in the early recovery of COVID-19 patients. 14 , 15 , 16 These findings suggest the importance of understanding the dynamics of TAMs in longitudinal studies with respect to the COVID-19 patients who were exposed to the virus during several waves, and if so, how this could be coupled to the severity of the disease and the patients' clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%